O gênero comentário interpretativo-crítico em redações do vestibular da Unioeste: um estudo exploratório - Vaz, Alex Meneghete (2022)
The entrance exam writing is seen by many pre-university students as one of the most complex and challenging textual production practices by which high school graduates, who intend to apply for a place in a higher education course, from private or public Higher Education Institutions in the country, pass during the academic path. In addition, many institutions require the writing of copies of specific genres, as is the case of the Western Paraná State (Unioeste), which uses genres of predominantly argumentative typology in its essay tests, such as the opinion article, the letter from the reader and the interpretive-critical commentary (CIC), the latter being our object of study. Used for the first time in the writing test of the 2015 Entrance Exam Contest, CIC is the least chosen genre by university students in the Unioeste writing tests. This is due to the fact that it is a new genre and without totally equivalent copies circulating in the social sphere, in addition to not being a school genre, which leaves the entrance exam without theoretical or practical bases to produce an example of this genre. Therefore, the purpose of this qualitative research with an interpretive nature is to analyze copies of the CIC genre of the Unioeste writing test to identify its constitutive nature and describe its characteristics, in order to subsequently support pedagogical strategies in the classroom. In order to achieve this purpose, the following specific objectives were outlined: explanation of the situational characteristics of the genre, analysis of a corpus of 25 essays belonging to the CIC genre and the elaboration of a Didactic Model of the CIC genre. The theoretical foundation of this research is based on the theoretical-methodological framework of Sociodiscursive Interactionism in the contributions of Textual Linguistics and Normative Grammar of the Portuguese Language. The theoretical contributions of Bronckart (2007), proponent of the ISD Cristovão (2001) and Machado (2004, 2009), were especially useful for this research. Regarding the didactic model used in the research, the investigation was based on Cristovão et al. (2006), which approach the MDG based on the analysis recommended by the ISD, Dolz and Schneuwly (2004), Pietro, Érard and Kaneman-Pougatch (1996/1997) and Pietro and Schneuwly (2003) and Adam (2011, 2019). Based on the results obtained from the analysis of the CIC, we have, as main characteristics of the prototypical CIC, the use of a basic structure of essays of argumentative typology entrance exams (introduction, development and conclusion) and its constitutive elements - the thesis / point of view, arguments and the closure of ideas. In addition, there are retakes of the analyzed/commented/interpreted text or of the theme, proposed by the consignment, throughout the writing, some interdisciplinary argumentative strategies and greater adherence to the correction criteria of the Unioeste examining board. It is expected that the MDG proposal of the CIC genre made throughout this dissertation can help teachers of basic education or preparatory courses, for example, to develop teaching strategies for the production of CIC aimed at the writing test of Unioeste's Entrance Exams.